Differentiation of the retinal morphology aging trajectories in schizophrenia and their associations with cognitive dysfunctions - Domagała, Adam; Domagała, Lucyna; Kopiś-Posiej, Natalia; Harciarek, Michał; Krukow, Paweł (Frontiers in Psychiatry, 2023)
Previous studies evaluating the morphology of the selected retinal layers in schizophrenia showed abnormalities regarding macular thickness, retinal nerve fiber layer (RNLF), and ganglion cell complex (GCC). Concurrently, accumulating neuroimaging results suggest that structural alterations of the brain in this disease might be an effect of accelerated aging. Referring to these findings, we aimed to determine whether the thinning of the retinal layers assessed with the Optic Coherence Tomography (OCT) in a group of schizophrenia patients (n = 60) presents a significant age-related decrease exceeding potential changes noted in the control group (n = 61). Samples of patients and controls were divided into three age subgroups (younger, middle-aged, and older). OCT outcomes, such as macular thickness and volume, macular RNFL, peripapillary RNFL, and GCC were analyzed concerning a diagnosis status (controls versus patients) and age subgroups. Additionally, associations between retinal parameters, age, and selected cognitive functions were evaluated. Post hoc tests revealed that macular thickness and volume in patients undergo significant are-dependent thinning, which was not observed in the control group. Regression analyses confirmed the association between macular morphology and age. Selected speed-dependent cognitive functions in patients decreased significantly with age and these features were also significantly associated with some OCT outcomes also after controlling for antipsychotic treatment. Our results suggest that reduced measures of retinal structure detected in schizophrenia may be an effect of accelerated aging, however, further research is needed using computational solutions derived from brain imaging studies based on large datasets covering representatives of all age groups.